Efficacy and Safety of New Oral Anticoagulants versus Warfarin in the Resolution of Atrial Fibrillation with Left Atrial/Left Atrial Appendage Thrombus: A Systematic Review and Meta-Analysis - Guan-lian Mo; Jing Wen; Yu-yu Ye; Yong-qi Lu; Tian-ming Gan; Ying-jie Yang; Jin-yi Li (Reviews in Cardiovascular Medicine)
Background: To compare the efficacy and safety of novel oral anticoagulants (NOACs) and vitamin K antagonists (VKAs) in nonvalvular atrial fibrillation (NVAF) patients with left atrial/left atrial thrombosis through a systematic review and meta-analysis. Methods: The CBM (China Biology Medicine disc), CNKI (China National Knowledge Infrastructure), VIP (Chinese Technology Periodical Database), Wanfang, PubMed, Embase, Cochrane Library, and Web of Science databases were searched for relevant studies from their inception to June 30, 2022. Results: Twelve articles (eight cohort studies and four randomized controlled trials) involving 982 patients were included. Meta-analysis showed that NOACs had a significantly higher thrombolysis rate than VKAs (78.0% vs. 63.5%, odds ratio (OR) = 2.32, 95% confidence interval (CI) 1.71 to 3.15, p < 0.0001). Subgroup analysis revealed rivaroxaban to be more effective than VKAs, whereas there was no significant difference between dabigatran and apixaban. There were no significant differences in embolic events, bleeding, or all-cause mortality. Thrombus resolution analysis showed higher left ventricular end-diastolic diameter and smaller left atrial diameter in the effective group than in the ineffective group. Conclusions: NOACs are more effective in thrombolysis than VKAs in NVAF patients with left atrial thrombosis, and there is no increased risk of adverse events compared with VKAs.